Pengaruh Insentif Pajak dan Penilaian Ekuitas Terhadap Konservatisme Akuntansi - Syifa Rustianti Nurhasanah; Dirvi Surya Abbas; Sigit Budi Santoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to determine the effect of tax incentives and equity valuations on accounting conservatism. The period used in this research is 5 (five) years, starting from 2014-2018. This research is a quantitative research. The sample in this study were 18 manufacturing companies. The sampling technique used was purposive sampling technique. The analysis technique used is panel data regression analysis using Eviews 9 software. The results of variable testing (X1) show tax incentives with t-statistic value (0.459250) <t table (1.98793) and Prob value 0.6733> 0, 05, it can be concluded that the tax incentive variable in this study has no influence on accounting conservatism. The results of variable testing (X3) show equity valuation with t-statistic value (0.375505) <t table (1.98793) and Prob value 0.7082> 0.05, it can be concluded that the equity valuation variable, in this study has no effect. against accounting conservatism. The test results collectively show the F-statistic value (8.566559)> F Table (2.71) and the Prob value. (F-statistic) 0.000049 <0.05, it can be concluded that H4 is accepted, which means that the independent variables in this study consisting of tax incentives and equity valuations together have an influence on accounting conservatism.